Bio-perceptions of Hydro carbon contaminated soil and its Bioremediation effect with Biological Consortia - Aswathy Chandran; Dr.S.Sujatha Jeyapaul (Newinera Publisher, 2020)
The present research work has clearly denoted as initially estimation of physic-chemical properties of the experimental hydrocarbon contaminated soil. The texture of the soil plays a very important role in microbial and plant species establishment and development and also influences physical parameters of the soil. The current results are clearly showed experimental soil of the hydrocarbon contaminated soil possessed totally eight different autochthonus bacterial strains were provably identified viz., Acinetobacter, Mycobacterium sp., Bacillus sp., Pseudomonas sp., and Aeromonas sp., observed by Bergy’s Manual. When this experimental soil was remediated with two biological sources such as four allothonus bacterial strains named as Enterobacter sp., Flavobacter sp., Shigella sp., and Bacillus sp., along with agronomic wastes also addition with neem juice. From the present result showed that Enterobacter sp., subjected polluted soil was remediated maximum than other treated sources assessed by spectrometric data. While, the biofilm formation experiment also been definitely expressed biodegradation potential enriched allothonus bacterial strain was the following order Enterobacter sp., Flavobacter sp., Shigella sp., and Bacillus sp.,. Moreover, other interesting finding also had been profounded such as dominant Antagonistic activity potential possessed autochthonus bacterial strain from the hydrocarbon contaminated soil. It has been identified through the molecular identification those typical organism expressed the named as ‘’Pseudomonas aeruginosa PA96’’by 16sr RNA sequence analysis. Additionaly maximum and maximum antagonistic activity has been noticed on E.coli, more or less similar zone of inhibition showed on other bacterial species of Shijella sp., and K. pneumonia. Moreover, HPLC results were almost elucidated fractions of hydrocarbon compounds thoroughly replied total illustrated chemical compounds are gradually minimized, when the heavy contaminated soils subjected with other bacterial sources along with various agronomic wastes. It has been significantly reduced the spectrum of the total hydrocarbon derivatives when it compared with before treatment of the contaminated soils. Therefore, these allothonous bacterial organism Enterobacter sp., strains could be considered for future use for bioremediation of oil contaminated land. However, further studies are needed to evaluate the potential of the isolated strains to degrade hydrocarbons in situ, in natural environmental conditions. This could be equally applicable for any allothonously present or other bacterial strains ubiquitously available in nature, and the technology could be further developed for targeting of any pollutants present on earth creating enormous environmental and health hazards.